Short-term treatment effects produced by the herbst appliance in the mixed dentition - Rodrigues de Almeida, Marcio; Henriques, José Fernando Castanha; Rodrigues de Almeida, Renato; Ursi, Weber [UNESP]; McNamara Jr., James A. (My University, 2005)
This prospective clinical investigation evaluates the dentoalveolar and skeletal cephalometric changes produced by the Herbst appliance during treatment of mixed dentition patients with Class II division 1 malocclusion. Thirty individuals (15 male and 15 female individuals; initial mean age nine years 10 months) were treated with the Herbst appliance for a period of 12 months. For comparison, the records of 30 untreated Class II children (15 boys, 15 girls; initial mean age nine years eight months) were followed without treatment for a period of 12 months. The results indicated that the treatment effects produced in the mixed dentition patients were primarily dentoalveolar in nature. The mandibular incisors were tipped labially, and the maxillary incisors were retruded; a significant increase in mandibular posterior dentoalveolar height occurred, and there was a restriction in the vertical development of the maxillary molars. There was no difference in the forward growth of the maxilla between the two groups. In comparison with the controls, however, the Herbst treatment produced a modest but statistically significant increase in total mandibular length. This increase in total mandibular length, however, was less than that observed in adolescent Herbst patients in other studies. © 2005 by The EH Angle Education and Research Foundation, Inc.
Keywords: Class II division 1 malocclusion; Early treatment; Functional orthopedics; Herbst appliance; Mixed dentition; cephalometry; clinical article; comparative study; controlled study; dentition; female; human; incisor; male; malocclusion; mandible; maxilla; molar tooth; prospective study; school child; statistical significance; Cephalometry; Child; Dentition, Mixed; Female; Humans; Incisor; Male; Malocclusion, Angle Class II; Mandibular Advancement; Maxillofacial Development; Molar; Orthodontic Appliances, Functional; Orthodontics, Interceptive; Prospective Studies; Treatment Outcome; Vertical Dimension